2011
DOI: 10.1103/physrevlett.106.153001
|View full text |Cite
|
Sign up to set email alerts
|

Proton Size Anomaly

Abstract: A measurement of the Lamb shift in muonic hydrogen yields a charge radius of the proton that is smaller than the CODATA value by about 5 standard deviations. We explore the possibility that new scalar, pseudoscalar, vector, and tensor flavor-conserving nonuniversal interactions may be responsible for the discrepancy. We consider exotic particles that, among leptons, couple preferentially to muons and mediate an attractive nucleon-muon interaction. We find that the many constraints from low energy data disfavor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 39 publications
5
139
0
1
Order By: Relevance
“…Further noted in [7], neutron scattering constraints only limit models with very light new particle masses (under 5 MeV), other muonic atom energy splittings give bounds already below ones discussed, the π → γV decay where V is a massive vector only impacts an m V mass range that is already excluded, and the limits from nonobservance of the decay η → V V is not serious for m V below m η /2 given the results in Figs. 1 and 2.…”
Section: Closing Commentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Further noted in [7], neutron scattering constraints only limit models with very light new particle masses (under 5 MeV), other muonic atom energy splittings give bounds already below ones discussed, the π → γV decay where V is a massive vector only impacts an m V mass range that is already excluded, and the limits from nonobservance of the decay η → V V is not serious for m V below m η /2 given the results in Figs. 1 and 2.…”
Section: Closing Commentsmentioning
confidence: 89%
“…They showed that in first order of nonrelativistic perturbation theory, exchange particle masses of order MeV could produce the observed Lamb shift, albeit exchanges with masses this light run afoul of neutron scattering data if the neutron and proton have similar coupling. Barger et al [7] also considered new scalar and vector particles, but suggested it would be difficult for them to satisfy additional constraints placed by Υ, J/ψ, π, and η-decays.…”
mentioning
confidence: 99%
“…A fairly obvious use for contact interactions in the point-particle action is to parametrize the effects of any hypothetical new forces acting between nuclei and electrons or muons, and in particular forces that differ in strength between these two (since these can be captured through species-dependent values for c s and c v , unlike for r p ). Indeed the observation that the existence of such short-range interactions could, in principle, explain the proton radius puzzle [38][39][40] has led to efforts to better understand their size [53] and to the proposal of exotic interactions of this type [62][63][64][65].…”
Section: Jhep09(2017)007mentioning
confidence: 99%
“…The perhaps most tantalizing deviation occurs in the ratio R K = B(B + → K + µ + µ − )/B(B + → K + e + e − ), which was observed about 2.6 σ below the theoretically clean SM prediction, 1 We do not consider the proton size anomaly observed in muonic hydrogen atoms [6]. NP interpretations of this measurement are very challenging [7,8].…”
Section: Introductionmentioning
confidence: 99%